Examining the status of prison libraries around the world: A literature review. (March 2023) - Hussain, Syed Tauseef; Batool, Syeda Hina; Rehman, Ata ur; Zahra, Syeda Kiran; Mahmood, Khalid
The purpose of this study is to review the published literature and highlight the situation of prison libraries around the world. The study strives to adopt a comprehensive approach while reviewing the literature in order to survey the present status geographically. The available published literature on prison libraries in local and international library and information science journals has been reviewed. The researchers also consulted other sources, such as books, theses, dissertations, conference proceedings, library websites, individuals and professional organizations, including the American Library Association, Association of College and Research Libraries, and IFLA. The databases used included Library and Information Science Abstracts, Library, Information Science and Technology Abstracts, Emerald, JSTOR, Google Scholar and ResearchGate. The keywords used for searching can be categorized as 'prison libraries', 'jail libraries', 'correctional institution libraries' and 'rehabilitation centres'. Overall, findings suggest that the situation of prison libraries in USA, UK, Europe and Asia (only urban areas) is much better as compared to the other regions of the world. This situation is because of the availability of resources, access to the Internet, technology, automated catalogues, cooperation with other libraries such as public libraries, and regular budgets to run library affairs smoothly. A lack of professional staff, the unavailability of library space, limited collections, censorship issues, a poor budgetary situation, the absence of library associations in developing countries, and a lack of cooperation among prison libraries and public libraries are the major causes of the current situation of prison libraries. The study is unique in nature as it highlights the situation of prison libraries worldwide through a wide lens, focusing on standards, services and difficulties, as well as recommendations made by the researchers.